2009
DOI: 10.4314/ajbr.v9i3.48898
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of back pain among pregnant women attending ante-natal clinics in selected health care facilities

Abstract: Back pain is (BP) is recognized as an important problem in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 30 publications
1
28
0
4
Order By: Relevance
“…LBP in pregnancy is exacerbated by the softening of the ligaments and joints of the lumbosacrum occasioned by the elevated progesterone and relaxin amongst others in pregnancy (Mac Evilly and Buggy, 1996;Kristiansson et al, 1996;Ayanniyi et al, 2006;Endresen, 1995;Ostgaard, 1996;Darry et al, 2007). Movements across these joints can become very painful particularly in pregnancy; this is worsened by the exaggerated lordosis of pregnancy, increased load on the lower spine and the upper femoral heads (Joanne et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LBP in pregnancy is exacerbated by the softening of the ligaments and joints of the lumbosacrum occasioned by the elevated progesterone and relaxin amongst others in pregnancy (Mac Evilly and Buggy, 1996;Kristiansson et al, 1996;Ayanniyi et al, 2006;Endresen, 1995;Ostgaard, 1996;Darry et al, 2007). Movements across these joints can become very painful particularly in pregnancy; this is worsened by the exaggerated lordosis of pregnancy, increased load on the lower spine and the upper femoral heads (Joanne et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that following the birth, a woman's posture returns to the way that it was in pre-pregnancy. However, some studies have shown that the posture after pregnancy is not significantly different to the posture developed during the later stage of pregnancy (Mac Evilly and Buggy, 1996;Kristiansson et al, 1996;Ayanniyi et al, 2006;Endresen, 1995;Darry et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like many other studies on prevalence of lower back pain, the present study included only people who were able to read and understand the local language (Hindi) [5,10,14]. Considering the previous literature available, we excluded the housewives who were engaged in any sort of occupational activity other than household work, and also those who were pregnant or diagnosed with diabetes or neurological, cardiovascular or psychiatric disorders [6,[15][16][17][18][19]. Housewives with tumor, infection, or any major trauma to the spine causing fracture were also excluded from study [20].…”
Section: Methodsmentioning
confidence: 99%
“…These changes include weight gain, changes in posture, weakness of joints and ligaments and musculotendinous stretch [1]. The incidence of back pain in pregnant women is very high, about 30-70% [2][3][4][5]. It is also found that 31.7% of pregnant women have pubic symphysis pain.…”
Section: Introductionmentioning
confidence: 91%